Woman Representation in Tangled Film - Rahajeng Herningtyas Woro Utamie (Universitas Pendidikan Indonesia (UPI), 2014)
The present study entitled Woman Representation in Tangled Film aims at examining and making meaning of the representation of woman in Tangled film. Utilizing a qualitative research, particularly a descriptive method, the present study adopts Kellie Heintz and Mark Stracey’s (2006) film studies theory and women representation theory by Brittany N Maggiore (2003). There are a lot of studies about women representation but only a few which discusses women representation using film studies. Therefore, this present study highlights women representation from different perspective because this study uses a film as the subject of the research to see woman representation by using the language of film, such as camera shot, camera angle and mise en scene. From the analysis, there are three aspects which shows woman representation in Tangled film, such as Rapunzel’s physical appearance, personal traits, and her relation to other characters. Through the language of film, the woman representation in Tangled film is constructed in more detail because the element used by the filmmaker made the figure more highlighted. Meanwhile, the woman representation theory also strengthens the depiction of woman representation in Tangled film. This film offers a new portrayal of woman representation which shows a beautiful woman who has ability in language.Keywords: Camera Angle, Camera Shot, Film, Film Studies, Mise En Scene, Rapunzel, Tangled, Woman, Woman Representation